Policy and competitiveness of agroforestrybased technologies for maize production in Cameroon: an application of policy analysis matrix - Adesina, A.A.; Coulibaly, O. (Wiley, 1998)
Questions have been raised about the ecological consequences and economic sustainability of exclusive reliance on chemical fertilizers for the rapidly expanding maize production across sub-Saharan Africa. Alternative agroforestry-based natural resource management technologies have been developed for farmers. This paper applies the policy analysis matrix (PAM) to analyze the social profitability of agroforestry-based technologies for maize production in the highland savanna zone of Cameroon, and the impacts of policy shifts on the financial competitiveness of maize production under these technologies. The paper shows that maize production under agroforestry-based systems has high comparative advantage.